IbM BAGI KELOMPOK PENGRAJIN PEMBUAT PERALATAN DAPUR DI DESA KEPATIHAN TULUNGAGUNG JAWA TIMUR - Rulirianto Rulirianto; Bambang Irawan; Heru Utomo (Publisher UPT P2M Politeknik Negeri Malang, 2016)
Kitchen Appliance maker Craftsmen group is a group of productive people who daily make kitchen tools such as the cormorant, pots, pans, bread oven, stove. In the course of production using very basic equipment and even many of these self-made equipment. Manually production activities and acquired skills passed down from their parents.Implementation Activities IbM with the introduction of production techniques by means of